CCNA 200-301. Official cert guide. Volume 2 - Odom, Wendell; Gooley, Jason; Hucaby, David (Hoboken, New Jersey : Cisco Press, 2025)
"CCNA 200-301 Official Cert Guide, Volume 2 from Cisco Press enables you to succeed on the Cisco exam the first time and is the only self-study resource approved by Cisco. Best-selling author Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills"--
Includes index.
CSE
Keywords: Internetworking (Telecommunication) -- Examinations -- Study guides; Electronic data processing personnel -- Certification; Computer networks -- Management -- Examinations -- Study guides; Computer security -- Examinations -- Study guides; Computer science